Comparing preference related to comfort in torque-matched muscle contractions between two different types of functional electrical stimulation pulses in able-bodied participants. (30th September 2021) - Garcia-Garcia, Martha G.; Jovanovic, Lazar I.; Popovic, Milos R.
Abstract : Context/Objective: Functional electrical stimulation (FES) is commonly used in rehabilitation to generate electrically-induced muscle contractions. FES has been shown to assist in the recovery of voluntary motor functions after stroke or spinal cord injury. However, discomfort associated with FES can motivate patients to withdraw their participation from FES therapy despite its benefits. To address this issue, a functional electrical stimulator, called MyndMove™ (MyndTec Inc., Canada), has been developed to generate more comfortable contractions than conventional stimulators. Design: Cross-sectional, interventional, with two treatment arms. Setting: A laboratory within a rehabilitation center. Participants: Twelve able-bodied participants. Intervention: FES delivered with two different stimulators, MyndMove™ and Compex Motion (Compex, Switzerland), during muscle contractions of high, moderate and low stimulation intensity. Outcome Measures: Comfort-related preference to a given stimulator and the discomfort score rated through a Numeric Rating Scale (NRS-101) for both stimulators. Results: Participants perceived a reduction in discomfort during high-intensity stimulation generated using MyndMove™. In addition, MyndMove™ stimulations were preferred in 60% of all contractions. The reduction in discomfort associated with MyndMove™ might be due the fact that MyndMove™ delivers less charge to generate contractions of equivalent intensity, compared to Compex Motion. Conclusion: Reducing discomfort during FES may help in generating stronger and more clinically useful contractions, increasing accessibility of FES therapy to include individuals with low tolerance to FES.